2019
DOI: 10.1007/s00233-019-10050-z
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphisms, dominions and $$\mathcal {H}$$-commutative semigroups

Abstract: In the present paper, a series of results and examples that explore the structural features of H-commutative semigroups are provided. We also generalize a result of Isbell from commutative semigroups to H-commutative semigroups by showing that the dominion of an H-commutative semigroup is H-commutative. We then use this to generalize Howie and Isbell's result that any H-commutative semigroup satisfying the minimum condition on principal ideals is saturated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Moreover, Shah et al [9] have shown that classes of structurally (n, m)-generalized inverse semigroups are saturated as well. Furthermore, Alam et al [10] have extended Howie's and Isbell's result to show that any H-commutative semigroup satisfying the minimum condition on principal ideals is saturated. In a related direction, Ahanger et al [11] have established the saturation of generalized left [right] regular semigroups.…”
Section: Theorem 5 ([6] (Theorem 54))mentioning
confidence: 99%
“…Moreover, Shah et al [9] have shown that classes of structurally (n, m)-generalized inverse semigroups are saturated as well. Furthermore, Alam et al [10] have extended Howie's and Isbell's result to show that any H-commutative semigroup satisfying the minimum condition on principal ideals is saturated. In a related direction, Ahanger et al [11] have established the saturation of generalized left [right] regular semigroups.…”
Section: Theorem 5 ([6] (Theorem 54))mentioning
confidence: 99%
“…1,18). Recently, the structure of semigroups of this class has been explored by Alam, Higgins, and Khan [5].…”
Section: Preliminariesmentioning
confidence: 99%
“…In [4], Alam and Khan have shown that the variety of semigroups satisfying the identity x y = x yx [yx = x yx] is closed. Next we generalize this result by showing that for each n ≥ 2 ∈ N, the variety of semigroups satisfying the identity…”
Section: Lemma 28 For All Kmentioning
confidence: 99%